2020
DOI: 10.3390/jcm9062011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Psychological Impact of COVID-19 Infection in Adult Patients with Eosinophilic Gastrointestinal Disorders during the SARS-CoV-2 Outbreak

Abstract: Eosinophilic gastrointestinal diseases (EGIDs) are chronic gastrointestinal conditions requiring corticosteroid and immunosuppressive therapy for disease control. Patients with EGIDs usually report impaired quality of life. We aimed to report the clinical and psychological impact of COVID-19 infection in EGID patients. In this prospective web-based study we invited all consecutive EGID patients attending the University Hospital of Salerno (Campania) and Padua (Veneto) to fill an ad hoc COVID-19 survey. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…In patients with type 2 diabetes in a rural community, telemedicine was found to be a useful tool to share educational and treatment approaches with the diabetes team, also improving HbA1c values (55). Telemedicine tools were also demonstrated to be adaptable for direct consultation in other healthcare environments (56,57) and in access-poor populations (58). Through telemedicine, we maintained social distancing, minimized the risk of SARS-CoV-2 transmission, and suggested to patients the strategies to pursue the better glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with type 2 diabetes in a rural community, telemedicine was found to be a useful tool to share educational and treatment approaches with the diabetes team, also improving HbA1c values (55). Telemedicine tools were also demonstrated to be adaptable for direct consultation in other healthcare environments (56,57) and in access-poor populations (58). Through telemedicine, we maintained social distancing, minimized the risk of SARS-CoV-2 transmission, and suggested to patients the strategies to pursue the better glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Chiang et al [ 102 ] reported a diminished expression of ACE2 in esophageal tissue from adults with eosinophilic esophagitis (EoE) compared to healthy controls. While the number of patients that have been evaluated remains limited, Savarino et al [ 103 , 104 ] reported that a diagnosis of EGID presents no specific increased (or decreased) risk with respect to prognosis and outcomes of SARS-CoV-2 infection.…”
Section: Covid-19 In Patients With Eosinophil-associated Diseases Andmentioning
confidence: 99%
“…5,6 Early attempts to assess the COVID-19 burden in patients with eosinophilic esophagitis (EoE) and eosinophilic gastrointestinal diseases (EGIDs), whose main disease pathology is concentrated in tissues expressing the proteins necessary for viral invasion, failed to identify SARS-CoV-2 infected EoE/EGID patients. [7][8][9] Not only do EoE/EGIDs involve organs involved in SARS-CoV-2 infection, but they are also a form of immune dysregulation, and their mainstay treatments involve medications (proton pump inhibitors [PPIs] and steroids) that have been implicated in the risk for more severe COVID-19. [10][11][12][13] Furthermore, although normal and elevated peripheral eosinophil counts have been found to be associated with better outcomes in COVID-19, 14,15 it is theoretically possible that eosinophil depleting drugs, which are sometimes used for treatment of EoE/EGIDs, may induce more severe disease.…”
mentioning
confidence: 99%